INTERVENTION IN THE POMBALINE LIVING SPACE THROUGH SUSTAINABLE ATTITUDE - Graça, Daniela (European Scientific Journal, ESJ, 2015)
During the last decades, Lisbon’s downtown population has decreased considerably. Its current residents are mostly older people, whose economic and social situations are brittle. Although they are the ones who allow traditions and cultural values to persevere, it is necessary to avoid the process of museification and to encourage the newer generations to inhabit this area. These new residents are characterised by a new life style, where working and leisure are beginning to merge. This makes it necessary to adapt the old living space to a new living and social reality. These buildings are a result of the XVIII century urban and architectural plan where every floor consisted of several small rooms with small dimensions, no longer necessary for today’s needs. The pombaline cage, originally built to be simply a structural system, can now serve new purposes. By inserting key elements from the pombaline period in the contemporary living space, the present becomes a stratum from multiple generations. Since Lisbon was rebuilt on large wooden stakes during this century, all the buildings’ structural systems had to be made of lightweight wood. Therefore, when selecting new materials for these buildings, it is important to consider the structure’s weight limitation without neglecting environmental impact. Furthermore, the current habitants’ lifestyle must not be disregarded when planning for the needs of the new residents. Through a social and economic sustainable attitude, a new business model is generated. This solves both housing needs and contributes to the enhancement of local employment.